Dilema Kewarganegaraan Ganda dalam Dinamika Hukum Internasional dan Implikasinya bagi Indonesia - Nabilah Rahmawati; Balqis Athyan Thadika Marchtika; Aulia Nur Azizah; Salsabila Firdaus (Amandemen: Jurnal Ilmu pertahanan, Politik dan Hukum Indonesia, 2025)
With the rise in human migration across national boundaries in the age of globalization, the issue of dual citizenship has become more and more important. Dual citizenship brings up a number of issues in the context of international law about legal status, diplomatic protection, and allegiance to both the nation of origin and the nation of residence. Increased cross-border social interactions that push people to hold several citizenships, technological improvements, and increased global economic integration have all complicated this dynamic. As a nation that upholds the idea of a single citizenship, Indonesia has trouble aligning its national laws with the shifting global legal framework, which governs things like dual citizenship, migration, and statelessness. is often more accepting of the practice of dual citizenship. From an international law standpoint, this research seeks to examine the subject of dual citizenship and its consequences for Indonesia's citizenship legislation and legal system. With a juridical-comparative examination of international legal instruments, scholarly publications, and applicable national legislation, the study uses a normative methodology. The results show that Indonesia's single citizenship concept conflicts with the worldwide trend that prioritizes human rights, diverse identities, and diaspora protection. Indonesia, according to the research, should think about changing its citizenship laws to take into account global concerns while still protecting its sovereignty, national stability, and core national values.